Creating knowledge : a monopoly? - Hall, Budd L.; Gillette, Arthur, 1938-; Tandon, Rajesh (New Delhi : Society for Participatory Research in Asia, 1982)
Contributed articles.
Includes bibliographical references.
Keywords: Economic development -- Sociological aspects -- Research; Rural development -- Sociological aspects -- Research; Social sciences -- Research -- Methodology